Evaluating Potential Importance of Cucumber (Cucumis sativus L. -Cucurbitaceae): A Brief Review - Mallick, Pushpa Karna (International Journal of Applied Sciences and Biotechnology, 2022)
Cucumber is a one of healthy fruit which have many health benefits of cucurbitaceae family. It maintains blood pressure, regulates hydration, controls sugar, and soothes the skin, helpful in digestion. It also helps to weight loss by reducing fat. Cucumber also contains fibre, potassium, manganese, magnesium and vitamin K, C, A. Cucumber can also have hydrated and antimicrobial properties, and detoxify the body and, prevent cancer and other many bone disease. Economically cucumbers are very important, as cucumbers contain high nutritional, medicinal as well as health beneficial values. In present presentation going to discussed about the economic importance of cucumber (Cucumis sativus). Int. J. Appl. Sci. Biotechnol. Vol 10(1): 12-15.